TANTANGAN DALAM PENYELENGGARAAN PELAYANAN PUBLIK YANG EFEKTIF PADA PANDEMI COVID 19 - Tan, Winsherly (Faculty of Law, Parahyangan Catholic University, 2021)
State or government affairs shall be conducted in accordance with the principles of good governance. This is considered a must in normal times and more so when the government have to deal with the COVID-19 pandemic. This general obligation is also in line with the theory proposed by Muchsan about the welfare state and the government’s obligation to provide public services. But reality shows a different picture. The Indonesian government seems to fail in providing good and reliable services in health care, public transport, social assistance, economy, and security. One solution proposed is to appoint a person in charge of managing public complaints. The expectation is that this will empower the public, raise public awareness and increase government capacity to provide for public services.